Philosophy : - Moore, Brooke Noel. (McGraw Hill Higher Education, 2002)
One of the most widely adopted texts in the field, Philosophy: The Power of Ideas offers a topical introduction to philosophy within an overarching historical framework. The goal of the authors is to make philosophy understandable while not oversimplifying the material, showing that philosophy contains powerful ideas that affect the lives of real people.